Activation of Antioxidant and Proteolytic Pathways in the Nigrostriatal Dopaminergic System After 3,4-Methylenedioxymethamphetamine Administration: Sex-Related Differences - Costa, Giulia; Caputi, Francesca Felicia; Serra, Marcello; Simola, Nicola; Rullo, Laura; Stamatakos, Serena; Sanna, Fabrizio; Germain, Marc; Martinoli, Maria-Grazia; Candeletti, Sanzio; Morelli, Micaela; Romualdi, Patrizia (Frontiers in Pharmacology, 2021)
3,4-Methylenedioxymethamphetamine (MDMA, “ecstasy”) is an amphetamine-related drug that may damage the dopaminergic nigrostriatal system. To investigate the mechanisms that sustain this toxic effect and ascertain their gender-dependence, we evaluated in the nigrostriatal system of MDMA-treated (4 × 20 mg/kg, 2 h apart) male and female mice the activity of superoxide dismutase (SOD), the gene expression of SOD type 1 and 2, together with SOD1/2 co-localization with tyrosine hydroxylase (TH)-positive neurons. In the same mice and brain areas, activity of glutathione peroxidase (GPx) and of β2/β5 subunits of the ubiquitin-proteasome system (UPS) were also evaluated. After MDMA, SOD1 increased in striatal TH-positive terminals, but not nigral neurons, of males and females, while SOD2 increased in striatal TH-positive terminals and nigral neurons of males only. Moreover, after MDMA, SOD1 gene expression increased in the midbrain of males and females, whereas SOD2 increased only in males. Finally, MDMA increased the SOD activity in the midbrain of females, without affecting GPx activity, decreased the β2/β5 activities in the striatum of males and the β2 activity in the midbrain of females. These results suggest that MDMA-induced neurotoxic effects are gender-dependent and dopaminergic neurons of males could be more sensitive to SOD2- and UPS-mediated toxic effects.